The Genomic DNA Immobilization on Microcrystalline Cellulose and its Application to Separate DNA-Binding Proteins from Kumquat (Fortunella margarita Swingle) - Yang, Hua; Li, Huang; Guo, Chun; Li, Meng-yun; Rao, Li-qun; Liu, Ting (Protein and Peptide Letters, 2014)
A method of immobilizing genomic DNA on microcrystalline cellulose was described to isolate DNA-binding proteins. At first, DNA fragments were prepared by sonication and immobilized on cellulose phase. After the immobilization, DNA duplex formation was done. Using this microcrystalline cellulose affinity chromatography technique, DNA-binding proteins from kumquat (Fortunella margarita Swingle) leaf samples were isolated and then analyzed by Liquid Chromatography–Mass Spectrometry (LC-MS/MS). LC-MS/MS analysis showed that twenty-eight kinds of protein mainly including histones, protein-synthetic proteins and other DNA-binding proteins were identified. The identification list consists with the results in previous research on DNA-binding proteins isolation. It further suggests that the technique developed in this study can be applied to the effective isolation of DNA-binding proteins.
Keywords: DNA-binding proteins